PENGARUH LOKASI DAN HARGA TERHADAP LOYALITAS MELALUI KEPUTUSAN PEMBELIAN PADA LAVAS’CO COFFEE AND RESTO DI KOTA TIMIKA - RESTY MADIA BATO'SAU' (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the eflect of location and price on loyalty through purchasing decisions at Lavas'co Coflee and Resto in Timika City. The data collected in this study are qualitative data and quantitative data sourced from Lavas'co Coflee and Resto in Timika City. The number of samples in this study was 100. Data collection techniques in this study were observation and questionnaires and used SEM-PLS (Structure Equation Model Partial Least Square) analysis and the application used SmartPLS Version 4.0. The results of the analysis show that location and price have a positive and significant eflect on purchasing decisions at Lavas'co Coflee and Resto. Location does not have a positive and significant eflect on consumer loyalty at Lavas'co Coflee and Resto, while price has a positive and significant eflect on consumer loyalty at Lavas'co Coflee and Resto. Purchasing decisions have a positive and significant eflect on consumer loyalty at Lavas'co Coflee and Resto. Location and price have a significant eflect on consumer loyalty through purchasing decisions at Lavas'co Coflee and Resto.